Synthesis Of Carbon Nanotubes Via Decomposition Of Methane Using Carbon Supported Catalysts - Murugaiyan, Sivakumar Vaiyazhipalayam (2011)
Carbon nanotubes (CNTs) with their special properties find applications in many areas. Owing to its global demand, its synthesis at a cheaper cost is inevitable. In this study, low-cost carbon materials like carbon molecular sieves (CMS-G, CMS-IN) and activated carbon (AC) were examined as supports for three different active metals (Ni, Co and Fe) for methane chemical vapour decomposition (m-CVD) process to produce CNTs. Blank studies and active metal impregnated (5, 10 and 15 wt% loadings) catalysts activity were studied at temperatures 650, 750 and 850 oC for maximum methane (CH4) conversion and optimum CNTs growth.